"Overwhelmed and out of my depth": Responses from early career midwives in the United Kingdom to the Work, Health and Emotional Lives of Midwives study. Issue 6 (November 2020) - Cull, Joanne; Hunter, Billie; Henley, Josie; Fenwick, Jennifer; Sidebotham, Mary
Abstract: Background: Efforts to resolve the longstanding and growing staffing crisis in midwifery in the United Kingdom have been hampered by very poor retention rates, with early career midwives the most likely to report burnout and intention to leave the profession. Aims: To establish the key, self-described factors of satisfaction and dissatisfaction at work for early career midwives in the United Kingdom, and suggest appropriate and effective retention strategies. Methods: Thematic analysis was undertaken on a subset of free text responses from midwives who had been qualified for five years or less, collected as part of the United Kingdom arm of the Work, Health and Emotional Lives of Midwives project. Findings: Midwives described feeling immense pressure caused by an unremittingly heavy workload and poor staffing. Where relationships with colleagues were strong, they were described as a protective factor against stress; conversely, negative working relationships compounded pressures. Despite the challenges, many of the midwives reported taking great pleasure in their work, describing it as a source of pride and self-esteem. Midwives valued being treated as individuals and having some control over their shift pattern and area of work. Discussion: These results, which reveal the strain on early career midwives, are consistent with the findings of other large studies on midwives' wellbeing. All available levers should be used to retain and motivate existing staff, and recruit new staff; in the meantime, considerable creativity and effort should be exercised to improve working conditions. Conclusion: This analysis provides a 'roadmap' for improving staff wellbeing and potentially retention.